Perancangan Ulang Tata Letak Fasilitas Produksi Tahu Untuk Meminimalkan Biaya Material Handling Menggunakan Algoritma Blocplan - Sihombing, Eric Agustian; Sutrisno, Sutrisno; Polewangi, Yudi Daeng (Universitas Medan Area, 2024)
Eric Agustian Sihombing 198150102, redesigning the layout of tofu facilities to minimize material handling costs using the blocplan algorithm. And guided by Mr. Sutrisno, ST., MT as Advisor 1 lecturer, Mr. Yudi Daeng Polewangi, ST., MT as Supervisor 2. Material transfer or material handling is an activity that is very important in production activities and has a close relationship with industrial facility layout planning. Therefore, material handling distances must be minimized by adjusting the layout of existing production facilities or departments. Pak Ponimin's small tofu industry is a business unit engaged in food production, especially tofu and its preparations. In the design process, the small tofu industry, Mr. Ponimin, did not consider factory efficiency, both in terms of the smooth movement of material movement and the placement of work stations, so obstacles were found in the form of high material handling costs due to the long distances for material handling. The purpose of this research is to redesign the layout of the tofu factory so as to produce a proposed layout with lower material handling costs. This research uses the blockplan algorithm method, the blockplan algorithm is a heuristic algorithm that uses both quantitative and qualitative data. This algorithm can be used to design the layout of facilities that are construction or improvement in nature. Where the algorithm can solve single story and story layout problems. Layout redesign begins with data collection in the form of department names, number of departments, broad needs of departments, and the degree of proximity that is poured into the activity relationship chart (ARC). Based on the Blocplan calculation analysis, 20 alternative proposed layouts were produced. The proposed layout chosen is the layout with the highest R–score, namely 0.93. Application of the proposed layout will reduce material handling costs from Rp. 16,713,840, - to x Rp. 10,939,920,- per month. The percentage of material handling cost savings is 15.8% per month